Perancangan dan Pengembangan Video untuk Aktivitas Dalam dan Luar Rumah untuk Mendukung Kesejahteraan Manula di Batam - Deli Deli; Yongki Wijaya (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Video as one of the developments in information technology that has the benefit of providing information and motivation for people to carry out an activity. One of the stages of human life is growing old as a senior, requiring activities aimed at developing his or her well-being. The method used to develop the video is Research and Development(R&D) and using Rowntree model. The contents of the video content are reading, caring for plants, playing chess and sports by seniors. The developed video has received a small group evaluation and a large group evaluation to get comments and suggestions regarding the necessary revisions. Based on user comments, the developed video has provided useful information regarding the activities of seniors